Rates and Cycles of Microbial Sulfate Reduction in the Hyper-Saline Dead Sea over the Last 200 kyrs from Sedimentary δ34S and δ18O(SO4) - Torfstein, Adi; Turchyn, Alexandra V. (Frontiers in Earth Science, 2017)
We report the 34S and 18O(SO4) values measured in gypsum, pyrite, and elemental sulfur through a 456-m thick sediment core from the center of the Dead Sea, representing the last ~200 kyrs, as well as from the exposed glacial outcrops of the Masada M1 section located on the margins of the modern Dead Sea. The results are used to explore and quantify the evolution of sulfur microbial metabolism in the Dead Sea and to reconstruct the lake’s water column configuration during the late Quaternary. Layers and laminae of primary gypsum, the main sulfur-bearing mineral in the sedimentary column, display the highest 34S and 18O(SO4) in the range of 13-28‰ and 13-30‰, respectively. Within this group, gypsum layers deposited during interglacials have lower 34S and 18O(SO4) relative to those associated with glacial or deglacial stages. The reduced sulfur phases, including chromium reducible sulfur, and secondary gypsum crystals are characterized by extremely low 34S in the range of -27 to +7‰. The 18O(SO4) of the secondary gypsum in the M1 outcrop ranges from 8 to 14‰. The relationship between 34S and 18O(SO4) of primary gypsum suggests that the rate of microbial sulfate reduction was lower during glacial relative to interglacial times. This suggests that the freshening of the lake during glacial wet intervals, and the subsequent rise in sulfate concentrations, slowed the rate of microbial metabolism. Alternatively, this could imply that sulfate-driven anaerobic methane oxidation, the dominant sulfur microbial metabolism today, is a feature of the hypersalinity in the modern Dead Sea. Sedimentary sulfides are quantitatively oxidized during epigenetic exposure, retaining the lower 34S signature; the 18O(SO4) of this secondary gypsum is controlled by oxygen atoms derived equally from atmospheric oxygen and from water, which is likely a unique feature in this hyperarid environment.